2010
DOI: 10.1590/s1413-81232010000700043
|View full text |Cite
|
Sign up to set email alerts
|

Vírus da hepatite B: avaliação da resposta sorológica à vacina em funcionários de limpeza de hospital-escola

Abstract: Vírus da hepatite B: avaliação da resposta sorológica à vacina em funcionários de limpeza de hospital-escola

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
14

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
1
5
0
14
Order By: Relevance
“…Moreover, no association was observed between seroconversion after three doses of vaccine and gender, as was shown in the research of Alavian et al 28 . However, associations of female gender with higher antibody titer values have been shown, as has been observed in previous studies 3,26 . The majority of studies have shown that a longer interval of time between the last dose of vaccine and undergoing the anti-HBs test leads to significant impact on the seroprotection indexes, with a better response being obtained when the seroconversion test was performed in up to 6 months after vaccination 2,26,28 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, no association was observed between seroconversion after three doses of vaccine and gender, as was shown in the research of Alavian et al 28 . However, associations of female gender with higher antibody titer values have been shown, as has been observed in previous studies 3,26 . The majority of studies have shown that a longer interval of time between the last dose of vaccine and undergoing the anti-HBs test leads to significant impact on the seroprotection indexes, with a better response being obtained when the seroconversion test was performed in up to 6 months after vaccination 2,26,28 .…”
Section: Discussionsupporting
confidence: 78%
“…Of these individuals, over 600,000 die every year of acute diseases or chronic sequelae secondary to infection by HBV [1][2] . Hepatitis B is an important public health problem on all continents 3 . In Brazil, in spite of the progression of vaccination coverage and increased access to guidance on prevention, approximately 17,000 cases are confirmed every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, pesquisas revelam que existe relação dos níveis de resposta vacinal com idade, sexo, tabagismo, diabetes, doença renal crônica (OSTI; MACHADO, 2010;MEDEIROS et al, 2011). Um estudo realizado com 104 funcionários de limpeza revela níveis menores de anti-HBs em fumantes e pessoas do sexo masculino (OSTI; MACHADO, 2010).…”
Section: Gutierrez 2007)unclassified
“…Um estudo realizado com 104 funcionários de limpeza revela níveis menores de anti-HBs em fumantes e pessoas do sexo masculino (OSTI; MACHADO, 2010).…”
Section: Gutierrez 2007)unclassified